Design of broadband Class E power amplifier in continuous operation modes. Issue 25 (1st December 2013) - Gao, Zhong; Liu, Chang; Guo, Guiliang; Chen, Hua; Luo, Chao; Han, Jingyu; Zhang, Lijun; Yan, Yuepeng
Abstract : Theoretically, constant output power and high DC‐to‐RF efficiency cannot be simultaneously achieved by a broadband Class E power amplifier (PA) even if the load network could provide the accurate impedance desired at each frequency point. Such a problem is solved with the presented concept of continuous Class E modes. New demands on the load and corresponding load network topology are discussed to provide a theoretical basis. To verify the feasibility, a prototype PA in TSMC 0.18 μm CMOS process is also presented. In the simulation, it exhibits a maximum output power of 18.7 dBm, a power added efficiency of 64–80% and an output power flattening of 0.5 dB in the frequency range from 360 to 610 M (52% of the central frequency). A comparison between it and a broadband parallel Class E PA implemented under the same conditions is also given.